Pencegahan Kekerasan di Kalangan Pemuda dan Remaja Jemaat GMIT Ebenhaezer Bilamun, Kabupaten Kupang Tengah - Mefibosed Radjah Pono; Arly E. M. de Haan (GOTAVA, 2024)
Community service activities at the Ebenhaezer Bilamun Congregation aim to increase awareness and knowledge about violence, provide initial knowledge for prevention, and create a safe environment for teenagers and young people. Using seminars, discussions, and awareness campaigns through social media, brochures and posters, 30 young people and teenagers aged 12-24 years, along with the congregation council with a participatory approach, were involved in this activity. They were given the opportunity to learn, understand and be aware of violence and how to prevent it. The results, through pre-tests and post-tests, showed that participants experienced changes in understanding and increased knowledge about violence. This activity increased their awareness of the dangers of violence, thus giving birth to a determination to prevent acts of violence. Thus, this activity not only helps young people and teenagers in broadening their horizons about violence, but also provides them with good provisions to protect themselves from acts of violence that they can do or receive from others. Likewise, the church can start planning programs to prevent violence and protect victims of violence. Overall, this coaching activity is an important step in the effort to create a safe and supportive community, improve the welfare and safety of congregation members, and create a stronger and more independent young generation in seeking to live peacefully and avoid acts of violence.